El uso profesional de la red social Twitter en la redacción del diario español El País (2014)
The article presents the results of a study on how the professional journalists of El Pais use the social networking service Twitter, the role this tool plays in their information-communication work, and the value they afford to it. The authors conclude the professionals in question see Twitter as being useful in their daily work and believe it has journalistic value and professional validity.